MAO-A Phenotype Effects Response Sensitivity and the Parietal Old/New Effect during Recognition Memory - Ross, Robert S.; Smolen, Andrew; Curran, Tim; Nyhus, Erika (Frontiers in Human Neuroscience, 2018)
A critical problem for developing personalized treatment plans for cognitive disruptions is the lack of understanding how individual differences influence cognition. Recognition memory is one cognitive ability that varies from person to person and that variation may be related to different genetic phenotypes. One gene that may impact recognition memory is the monoamine oxidase A gene (MAO-A), which influences the transcription rate of monoamine oxidase A. Examination of how MAO-A phenotypes impact behavioral and ERP correlates of recognition memory may help explain individual differences in recognition memory performance. Therefore, the current study uses electroencephalography (EEG) in combination with genetic phenotyping of the MAO-A gene to determine how well-characterized ERP components of recognition memory, the early frontal old/new effect, left parietal old/new effect, late frontal old/new effect, and the late posterior negativity are impacted by MAO-A phenotype during item and source memory. Our results show that individuals with the MAO-A phenotype leading to increased transcription have lower response sensitivity during both item and source memory. Additionally, during item memory the left parietal old/new effect is not present due to increased ERP amplitude for correct rejections. The results suggest that MAO-A phenotype changes EEG correlates of recognition memory and influences how well individuals differentiate between old and new items.